Water Stress in Plants - Mofizur Rahman, Ismail Md; Ara Begum, Zinnat; Hasegawa, Hiroshi (IntechOpen, 2016)
Water stress in plants is caused by the water deficit, as induced possibly by drought or high soil salinity. The prime consequence of water stress in plants is the disruption in the agricultural production, resulting in food shortage. The plants, however, try to adapt to the stress conditions using biochemical and physiological interventions. The edited compilation is an attempt to provide new insights into the mechanism and adaptation aspects of water stress in plants through a thoughtful mixture of viewpoints. We hope that the content of the book will be useful for the researchers working with the plant diversity-related environmental aspects and also provide suggestions for the strategists.